Virulence factor regulator (Vfr) controls virulence‐associated phenotypes in Pseudomonas syringae pv. tabaci 6605 by a quorum sensing‐independent mechanism. (12th November 2012) - Taguchi, Fumiko; Ichinose, Yuki
Summary Virulence factor regulator (Vfr) is a member of the cyclic 3′, 5′‐adenosine monophosphate (cAMP) receptor proteins that regulate the expression of many important virulence genes in Pseudomonas aeruginosa. The role of Vfr in pathogenicity has not been elucidated fully in phytopathogenic bacteria. To investigate the function of Vfr in Pseudomonas syringae pv. tabaci 6605, the vfr gene was disrupted. The virulence of the vfr mutant towards host tobacco plants was attenuated significantly, and the intracellular cAMP level was decreased. The vfr mutant reduced the expression of flagella‐, pili‐ and type III secretion system‐related genes and the defence response in nonhost Arabidopsis leaves. Furthermore, the expression levels of achromobactin‐related genes and the iron uptake ability were decreased, suggesting that Vfr regulates positively these virulence‐related genes. In contrast, the vfr mutant showed higher tolerance to antimicrobial compounds as a result of the enhanced expression of the resistance–nodulation–division family members, the mexA, mexB and oprM genes. We further demonstrated that the mutant strains of vfr and cyaA, an adenylate cyclase gene responsible for cAMP synthesis, showed a similar phenotype, suggesting that Vfr regulates virulence factors in a cAMP‐dependent manner. Because there was no significant difference in the production of acylhomoserine lactone (AHL) quorum sensing molecules in the wild‐type, vfr and cyaA mutant strains, Vfr might control important virulence factors by an AHL‐independent mechanism in an early stage of infection by this bacterium.